Emerging Technologies for Pulmonary Vein Isolation - Ramirez, F Daniel; Reddy, Vivek Y; Viswanathan, Raju; Hocini, Mélèze; Jaïs, Pierre (Circulation research, 2020)
Atrial fibrillation is the most common sustained cardiac arrhythmia and is associated with considerable morbidity and mortality. Electrically isolating the pulmonary veins from the left atrium by catheter ablation is superior to antiarrhythmic drug therapy for maintaining sinus rhythm, but its success varies depending on multiple factors, including arrhythmic burden. Although procedural outcomes have improved over the years, further gains are limited by a seemingly zero-sum relationship between effectiveness and safety, which is largely a product of the available technologies. Current energies used to create contiguous, transmural, and durable atrial lesions can result in serious complications if they reach the esophagus or phrenic nerve, for instance-structures that can be adjacent to the atrial myocardium, often within millimeters of the energy source. Consequently, high rates of pulmonary vein-left atrium reconnections are consistently seen in clinical studies and in clinical practice as operators appropriately forgo ablation effectiveness to protect patients from harm. However, as ablative technologies evolve to circumvent this stalemate, safer, and more effective pulmonary vein isolation seems increasingly realistic. Furthermore, the innovative nature of these technologies raises the prospect of markedly improved procedural efficiency, which could increase patient comfort, reduce operator occupational injuries, and enhance the use of health resources-all of which are increasingly important considerations particularly as the demand for catheter ablation for atrial fibrillation continues to rise. We herein review 3 promising candidate ablation technologies with the potential to revolutionize the management of patients with atrial fibrillation: electroporation (pulsed-field ablation), expandable lattice-tip radiofrequency ablation/electroporation, and ultra-low temperature cryoablation.
Keywords: catheter ablation; pulmonary veins; safety; efficiency; therapies, investigational; ablation techniques; Animals; Humans; atrial fibrillation; Catheter Ablation; lidé; Atrial Fibrillation; zvířata; venae pulmonales; Pulmonary Veins; fibrilace síní; katetrizační ablace